Food as a factor of fertility, development duration, and changes in morphometric parameters in Henosepilachna vigintioctomaculata (Motschulsky) - N. V. Matsishina; P. V. Fisenko; M. V. Ermak; O. A. Sobko; D. I. Volkov; A. G. Baleevskih (Овощи России, 2021)
Relevance.The physiology of insects nutrition and digestion reflects the diversity of their food specialization, aimed at the most effective use of feed. The choice of the object of nutrition is provided by attractants in it, as well as the presence of substances necessary for the insect to pass the stages of development and general nutrition. On the other hand, the “plant-phytophage” system has well-developed barriers that limit the choice of plants by insects for settling, feeding, and eggs laying. In the modern literature, there is very little information on the effect of food plants on fertility, development duration, and changes in morphometric parameters in 28-spotted potato ladybird Henosepilachna vigintioctomaculata (Motschulsky). However, they are important for understanding the ecology of the pest and developing effective control measures.Research methodology. The laboratory colony of Henosepilachna vigintioctomaculata (Motschulsky) was established in 2019. Adults were collected in various locations throughout Primorsky Territory, Russia. For an introduction into the culture of the insectarium, imagos, clutches, and larvae were collected in natural habitats. Standard methods of keeping and breeding insect cultures were used, aimed at optimizing the parameters of the environment, the density of the content, and the feed supply.Results. The uneven influence of crops on different aspects of the ontogenesis of the potato ladybird was revealed. The potato was the most favorable food in most experiments. When feeding with this crop, the smallest incubation period of eggs, the largest sizes of larvae of initial ages, the largest sizes of pupae, fertility, low mortality was observed, and as a result, the largest growth coefficient (3.22±0.22) and the shortest period of development from eggs to imago (21.3±0.81) were revealed. The remaining forage plants used in the study showed a less unambiguous result. The different influence of crops on both individual indicators and the ontogenetic periods of the phytophage was found. When eating tomato, cucumber, pumpkin, lime, high overall mortality was noted. At the same time, linden stimulated the development of eggs and the growth of young larvae but provoked low fertility and a general prolongation of the development period. According to the set of characteristics, pumpkin, cucumber, and linden were the least favorable for nutrition.